Influence of Influencer Post Characteristics through Peripheral Routes on Behavioral Intentions of TikTok Users - Maulana, Aziz Akram; Mahadian, Adi Bayu (eProceedings of Management, 2025)
AbstractThis study examines the influence of TikTok influencers' post characteristics on followers' behavioral intentionsthrough peripheral route mechanisms, using the Elaboration Likelihood Model (ELM) and the StimulusOrganism-Response (SOR) framework. By focusing on Indonesia, the country with the largest number of TikTokusers globally, this research addresses the limitations of previous studies conducted in Spain, which has a smalleruser base. The study explores how originality, quality, quantity, and humor in influencer posts impact hedonicexperiences and perceptions of opinion leadership, subsequently shaping behavioral intentions, such as the intentto follow accounts and advice. Data was collected through a survey of 420 followers of Fadil Jaidi, a topIndonesian TikTok influencer. The findings indicate that originality and humor significantly enhance hedonicexperiences and opinion leadership, which positively influence behavioral intentions. The study providestheoretical contributions to influencer marketing research and practical recommendations for influencers tooptimize content strategies on TikTok.Keywords: TikTok, influencers, post characteristics, peripheral route, behavioral intention.